2015
DOI: 10.1177/0363546515578250
|View full text |Cite
|
Sign up to set email alerts
|

Redefining “Critical” Bone Loss in Shoulder Instability

Abstract: While critical bone loss has yet to be defined for arthroscopic Bankart reconstruction, our data indicate that "critical" bone loss should be lower than the 20% to 25% threshold often cited. In our population with a high level of mandatory activity, bone loss above 13.5% led to a clinically significant decrease in WOSI scores consistent with an unacceptable outcome, even in patients who did not sustain a recurrence of their instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
206
3
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 488 publications
(229 citation statements)
references
References 45 publications
(73 reference statements)
6
206
3
14
Order By: Relevance
“…13,33,50 More recently, the lower limit of this bone loss has been questioned, with so-called “subcritical” bone loss of 13.5% leading to suboptimal outcomes with arthroscopic treatment. 58 Additionally, others have recommended use of the so-called “glenoid track” concept based off 3-dimensional CT reconstructions to preoperatively ascertain whether a Hill-Sachs lesion is engaging (ie, “off track”) and requires additional (eg, remplissage) or more aggressive initial management (Figure 1). 24,37,66 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,33,50 More recently, the lower limit of this bone loss has been questioned, with so-called “subcritical” bone loss of 13.5% leading to suboptimal outcomes with arthroscopic treatment. 58 Additionally, others have recommended use of the so-called “glenoid track” concept based off 3-dimensional CT reconstructions to preoperatively ascertain whether a Hill-Sachs lesion is engaging (ie, “off track”) and requires additional (eg, remplissage) or more aggressive initial management (Figure 1). 24,37,66 …”
Section: Discussionmentioning
confidence: 99%
“…63 Contrary to previously established thresholds, lower Western Ontario Shoulder Instability (WOSI) scores were seen after arthroscopic Bankart reconstruction in military patients with subcritical glenoid bone loss of greater than 13.5%, even in patients who did not sustain a recurrence of instability. 58 The additive effect of bipolar, subcritical bone loss compromises the biomechanical efficacy of the Bankart procedure, even with as little as 2 mm anterior glenoid defect. 1 These studies underscore the importance of patient-reported measures in outcome reporting, careful scrutiny of preoperative imaging, and personalized surgical management, as these extend beyond the traditional limited endpoints of instability recurrence and surgical revision.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who had greater than 13.5% GBL experienced significantly higher WOSI scores than would be considered clinically unacceptable with regard to their outcome even in the setting of no recurrence of instability. This led the authors to conclude that the threshold for bone loss should be redefined as a value less than 15%, especially in highly active patients [17]. Similarly Dickens et al investigated subcritical bone loss in American football players undergoing arthroscopic anterior shoulder stabilization.…”
Section: Indications/contraindicationsmentioning
confidence: 99%
“…More recently, though, subcritical levels of bone loss (≥13.5%) have been associated with poor functional outcomes in patients who did not experience recurrent instability, suggesting that the historic threshold of 20% to 25% glenoid bone loss representing the most important anatomic factor influencing the type of operative strategy employed should be re-evaluated using patient-reported outcome measures. 63 This may be pertinent to the epileptic population, who exhibit higher failure rates due to powerful uncontrolled seizures disrupting surgical repairs. 67…”
Section: Pathoanatomymentioning
confidence: 99%